Collaborative Governance in Strengthening Research-Based Regional Innovation Ecosystems: The Strategic Role of Bappeda of Tangerang Regency - Syamsoe Astra Negara; Effie Trisrtinawati; Alya Nurayu Sulisman; Christianto Deni Saputro; Yugni Maulana Aziz; Jaka Permana (Universitas Sultan Ageng Tirtayasa, 2026)
Strengthening a research-based regional innovation ecosystem has become increasingly important in addressing complex development challenges and improving regional competitiveness. This study aims to analyze collaborative governance in strengthening the research-based regional innovation ecosystem in Tangerang Regency, with a particular focus on the strategic role of the Regional Development Planning Agency (Bappeda). A qualitative approach with a case study design was employed, utilizing interviews, observations, and document analysis. The findings indicate that Bappeda plays a strategic role as a policy integrator, collaboration facilitator, knowledge broker, and orchestrator connecting development planning, research, innovation, and multi-stakeholder collaboration. The study also reveals that the sustainability of regional innovation depends on institutionalized collaboration, evidence-based policymaking, effective coordination, and the integration of innovation into planning and budgeting systems. Despite positive innovation achievements, challenges remain in inter-agency coordination, research utilization, human resource capacity, and stakeholder commitment. Strengthening collaborative governance is therefore essential to support sustainable regional development and enhance public welfare.